Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 Government of Gujarat - Planning Commission (Planning Commission, 1990)
According to the Projections of population provided in "Report of the Expert Committee on Population Projection" issued by the Office of the Registrar General of India, the population of the State would be 4.10 crores in 1991, 4.38 crores in 1996 and 4.65 crores in 2001. The population of the State is expected to grow to 4.86 crores by 2005 of which 1.86 crores (38.3%) would be the urban population.
Government of Gujarat, General Administration Department (Planning)